2014
DOI: 10.1210/jc.2013-4189
|View full text |Cite
|
Sign up to set email alerts
|

Masked and Overt Autoantibodies Specific to the DPD Epitope of 65-kDa Glutamate Decarboxylase (GAD65-DPD) Are Associated With Preserved β-Cell Functional Reserve in Ketosis-Prone Diabetes

Abstract: Masked GAD65Ab(DPD) are strongly associated with preserved β-cell functional reserve among patients with KPD. Absence of GAD65Ab(DPD) reactivity is associated with 2 HLA class II susceptibility haplotypes for autoimmune type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The HLA-DRB1*1501-DQB1*0601 haplotype has been associated with either the presence or increased quantity of immunoglobulins of the IgG, IgA and IgM families both in healthy controls and in disease, including total immunoglobulins (Ferreira et al, 2010), antibodies induced by viruses such as Epstein-Barr virus (Rubicz et al, 2013), and autoantibodies in type 1 diabetes (Ishii et al, 2005) and Sjo ¨gren syndrome (Gottenberg et al, 2003) though an opposite correlation is seen for few other antibody responses (Sundqvist et al, 2014). HLA-DQA1*0301, highly correlated with SNP rs34083746, is associated with autoantibody negative disease in ketosis-prone diabetes (Oak et al, 2014). SNP rs6457617 is a major susceptibility factor in rheumatoid arthritis and systemic sclerosis, independent of classical HLA alleles (The International MHC and Autoimmunity Genetics Network, 2009;Radstake et al, 2010;Allanore et al, 2011;Orozco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The HLA-DRB1*1501-DQB1*0601 haplotype has been associated with either the presence or increased quantity of immunoglobulins of the IgG, IgA and IgM families both in healthy controls and in disease, including total immunoglobulins (Ferreira et al, 2010), antibodies induced by viruses such as Epstein-Barr virus (Rubicz et al, 2013), and autoantibodies in type 1 diabetes (Ishii et al, 2005) and Sjo ¨gren syndrome (Gottenberg et al, 2003) though an opposite correlation is seen for few other antibody responses (Sundqvist et al, 2014). HLA-DQA1*0301, highly correlated with SNP rs34083746, is associated with autoantibody negative disease in ketosis-prone diabetes (Oak et al, 2014). SNP rs6457617 is a major susceptibility factor in rheumatoid arthritis and systemic sclerosis, independent of classical HLA alleles (The International MHC and Autoimmunity Genetics Network, 2009;Radstake et al, 2010;Allanore et al, 2011;Orozco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The more moderate clinical course of A+ß+ KPD patients compared with A+ß- KPD patients may be related in part to epitope-specific antibodies to the 65-kDa isoform of glutamic acid decarboxylase (GAD65)[ 12 ]. Furthermore, a specific amino-terminal epitope defined by monoclonal antibody DPD is correlated with a higher beta-cell functional reserve and was associated with the milder A+ß+[ 13 ]. However, the mechanisms that create the autoantibody specificity and result in variable beta-cell functional reserve remains to be known.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, the mechanisms that create the autoantibody specificity and result in variable beta-cell functional reserve remains to be known. In healthy individuals, GAD65 antibodies (GAD65Ab) are present in the sera but are masked by anti-idiotypic antibodies[ 13 ]. Masked GAD65Ab specific for the epitope DPD is strongly associated with preserved beta-cell function among patients with KPD[ 13 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…For example, up to four different phenotypes have been described in KPD, depending on the presence or absence of islet cell autoantibodies (A − or A + ) and ␤ cell functional reserve (␤ − or ␤ + ). 37 This classification, based on both immunologic and ␤ cell function criteria, has the highest accuracy and predictive value in classifying patients with KPD with regard to clinical outcomes and pathophysiologic subtypes. 38 In addition, a long-term longitudinal follow-up study including KPD A − ␤ + patients has revealed that this phenotype comprises two distinct subtypes distinguished by whether T1D-associated HLA susceptibility is present or not.…”
Section: Subclassification Of Type 2 Diabetesmentioning
confidence: 99%